Combining Stockholders' Equity Accounts Under Pooling of Interests Method. - Nurnberg, Hugo; Stickney, Clyde P.; Weil, Roman L. (The Accounting Review, 1975)
Abstract Illustrates the effects of both the purchase and pooling of interests methods of accounting for business combinations on post-combination financial statements. General rule for combining stockholders' equity accounts under the pooling of interests method; Exceptions to the general rule.